sj-pdf-1-pmj-10.1177_02692163221133977 – Supplemental material for Facilitating equitable access to hospice care in socially deprived areas: A mixed methods multiple case study - Maddy French; Thomas Keegan; Nancy Preston (SAGE Journals, 2022)
Supplemental material, sj-pdf-1-pmj-10.1177_02692163221133977 for Facilitating equitable access to hospice care in socially deprived areas: A mixed methods multiple case study by Maddy French, Thomas Keegan and Nancy Preston in Palliative Medicine
Keywords: 110308 Geriatrics and Gerontology; 111702 Aged Health Care